How to save time in surveillance without losing quality: comparison of two methods of surgical site infection surveillance in orthopaedic prosthetics in a French university hospital - Kuczewski, Elisabetta (J Infect Prev, 2020)
Surgical site infection (SSI) surveillance methods are not standardised and are often time-consuming. We compared an active method, based on orthopaedic department staff reporting suspected SSI, with a semi-automated method, based on computerised extraction of surgical revisions, after total hip and knee arthroplasty. Both methods allowed finding the same SSI cases. We found the same sensitivity but higher specificity with a straightforward time gain using the passive method. This represents an added value for the organisation of an effective SSI surveillance, based on existing hospital databases.